The Effect of Very High versus Very Low Sustained Loading on the Lower Back and Knees in Middle Life. (5th September 2013) - Milgrom, Yael; Milgrom, Charles; Constantini, Naama; Applbaum, Yaakov; Radeva-Petrova, Denitsa; Finestone, Aharon S.
Abstract : To evaluate the effect of the extremes of long term high and low physical activities on musculoskeletal heath in middle age, a historical cohort study was performed. The MRI knee and back findings of 25 randomly selected subjects who were inducted into the armed forces in 1983 and served at least 3 years as elite infantry soldiers were compared 25 years later, with 20 randomly selected subjects who were deferred from army service for full time religious studies at the same time. Both cohorts were from the same common genome. The two primary outcome measures were degenerative lumbar disc disease evaluated by the Pfirrmann score and degenerative knee changes evaluated by the WORMS score. At the 25-year follow up, the mean Pfirrmann score (8.6) for the L1 to S1 level of the elite infantry group was significantly higher than that of the sedentary group (6.7), (P = 0.003 ). There was no statistically significant difference between the WORMS knee scores between the two cohorts (P = 0.7 ). In spite of the much greater musculoskeletal loading history of the elite infantry cohort, only their lumbar spines but not their knees showed increased degenerative changes at middle age by MRI criteria.